SVEN STERKEN Y EVA WEYNS (eds.) - Territories of Faith. Religion, Urban Planning and Demographic Change in Post-War Europe - Delgado Orusco, Eduardo (ZARCH, 2024)
SVEN STERKEN, EVA WEYNS (eds.)Territories of Faith. Religion, Urban Planning and Demographic Change in Post-War EuropeLeuven University Press. Lovaina, 2022, 362 p. Tapa blanda, 59,72 €Idioma: inglésISBN: 9789462703094